Attitudes Associated to Types of Clauses in Texts of History. An Appraisal Theory Approach - Herrero Rivas, Luz Elena (Íkala, Revista de Lenguaje y Cultura, 2017)
This research report presents part of the results of a doctoral thesis about academic writing in Spanish within the area of history, following a systemic functional linguistics approach, particularly the transitivity system (Halliday & Matthiessen, 2014), and the Appraisal Theory (Martin & White, 2005), as of attitude assessing meanings. This study aimed to characterize academic language in academic essays at the undergraduate level and in research articles, by identifying their similarities and differences in expressing attitude (dimensions of affection, judgment, and appreciation), as well the relation between clause types in the transitivity system (material, relational, mental, verbal, existential and behavioral processes) present in those meanings. Using UAMCorpusTool software, transitivity was first analyzed in its quantitative and qualitative aspects, and then the types of attitude present in the types of clauses. The results showed that attitude types the most frequent in the area of history are appreciation and judgment, especially in material and relational clauses, while variations in mental and verbal clauses in expressing the types of attitude between corpora would be related to the level of experience in academic writing, genres and subject areas.